Diagnostic performance of lipid accumulation indices and triglyceride and glucose index for metabolic syndrome in a sample of Peruvian adult population: Rendimiento diagnóstico de los índices de acumulación lipídica y el índice triglicéridos y glucosa para síndrome metabólico en una muestra de pobladores adultos peruanos - Talavera, Jesús Enrique (2021)
Objectives: To determine the diagnostic performance of the lipid accumulation product (LAP), visceral adiposity index (VAI), triglyceride and glucose index (TyG) and body mass index (BMI) for metabolic syndrome (MetS) in a sample of Peruvian adults. Methodology: Study of diagnostic tests of the “National Survey on Nutritional, Biochemical, Socioeconomic, and Cultural Indicators related with Chronic Degenerative Diseases”. An analysis of ROC curves (Receptor Operation) was made, and their respective area under the curve (AUC) obtaining the different parameters such as sensitivity (Sens) and specificity (Spe). It was stratified according to sex and according to age. To choose the cut-off point, the Youden index was used. Results: The LAP had the highest AUC in both men (AUC = 0.929; cut-off value = 59.85; Sens = 91.6 and Spe = 84.5) and for women (AUC = 0.950; cut-off value = 53, 06; Sens = 92.4 and Spe = 86.4). The second place, in the case of men, was occupied by the VAI (AUC = 0.905; cut-off value = 2.36; Sens = 91.6 and Spe = 79.7), while in the case of women it was the TyG (AUC = 0.914; cut-off value = 8.70; Sens = 87.4 and Spe = 87.3). The LAP index showed significant differences with VAI to predict MetS (p < 0.05), while no differences were shown with TyG. Conclusion: The LAP index had the best diagnostic performance for MetS, both for men and women, regardless of age.